1 0 ( a 3 + b 2 + c ) If a , b and c are positive reals satisfying a b c = 1 , find the minimum value of the expression above. Round your answer to the nearest integer.
Part of the set
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution(+1).. But aren't a,b,c fixed in case of equality i.e equality occurs when: a = 3 2 ( 6 3 ( 2 ) 3 1 1 ) 1 1 2 b = 3 ( 6 3 ( 2 ) 3 1 1 ) 1 1 3 a n d c = 6 ( 6 3 ( 2 ) 3 1 1 ) 1 1 6
Log in to reply
If I remember correctly equality holds in AM-GM when all terms are equal to each other here 2 a 3 = 3 b 2 = 6 c and if you look carefully you will get the same result and you have just given me precise value of them.
Log in to reply
You have found the condition for equality as 2 a 3 = 3 b 2 = 6 c and given condition is a b c = 1 . Combining both, a,b,c are fixed.
Log in to reply
@Rishabh Jain – Duh, bro it's a b c = 1 look the question carefully
Log in to reply
@Department 8 – Just a typo.. : { Fixed...Now what say??
Log in to reply
@Rishabh Jain – Multiply them and you will see it's equal to 1
same way buddy.I guess both ironman and batman think the same way most of the time
Log in to reply
Working against wrong guys with technologically advanced things require the same skills.
Exactly Same Way
Same way. Why are you not coming to class
i did same
We assume that a = l and b = k when the equality holds
Using AM-GM we have a 3 + 2 l 3 ≥ 3 a l 2 and b 2 + k 2 ≥ 2 b k
So
a
3
+
b
2
+
c
≥
3
a
l
2
+
2
b
k
+
c
−
2
l
3
−
k
2
≥
3
3
6
l
2
k
−
2
l
3
−
k
2
Now k and l must satisfy
⎩
⎪
⎪
⎪
⎨
⎪
⎪
⎪
⎧
a
=
l
b
=
k
3
a
l
2
=
2
b
k
=
c
l
k
c
=
1
Solving and we get
⎩
⎪
⎪
⎪
⎪
⎨
⎪
⎪
⎪
⎪
⎧
l
=
1
1
2
7
2
k
=
2
3
1
1
(
2
7
2
)
3
c
=
3
1
1
(
2
7
2
)
3
So the minimum of the expression is
≈
2
7
.
0
4
5
.
.
.
which is
2
7
when rounded to the nearest integer
Problem Loading...
Note Loading...
Set Loading...
@Gurīdo Cuong , please tell me whether I did same as yours?
By AM-GM, we have
2 a 3 + 2 a 3 + 3 b 2 + 3 b 2 + 3 b 2 + 6 c + 6 c + 6 c + 6 c + 6 c + 6 c ≥ 1 1 1 1 2 2 × 3 3 × 6 6 ( a b c ) 6 1 0 ( a 3 + b 2 + c ) ≥ 1 1 0 1 1 2 8 × 3 9 1 ≈ 2 7 . 0 4 5
This means the minimum value of 1 0 ( a 3 + b 2 + c ) is approximately 27. Equality holds when 2 a 3 = 3 b 2 = 6 c